Factors affecting the speed of free writing. Issue 1 (2nd January 2013) - Ferrier, Jonathan; Horne, Joanna; Singleton, Chris
Abstract : Factors affecting the free writing speed of 11‐year‐old students were investigated using the Group and Individual Assessment of Handwriting Speed. Intelligence, gender, legibility and whether the student has special educational needs or speaks English as an additional language were all found to impact on writing speed to a significant extent. In one of the two schools studied, the students wrote significantly faster than the students in the other school. This 'teacher effect' was found to be independent of the other significant factors examined in the study and was attributed largely to instructional differences between schools and teachers. The average writing speed was 36% lower than published norms for this test, implying that 70.2% of the students would be eligible for extra time in examinations and raising doubts regarding the validity of these norms. It was concluded that vulnerability to teacher effects and other factors makes free writing an unreliable method of measuring writing speed, especially when group administered, and calls into question its use to justify the provision of examination access arrangements or accommodations.